2022
DOI: 10.3389/fimmu.2022.982786
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasomes control activation of innate immune signaling and microglial function

Abstract: Microglia are the resident immune cells of the central nervous system (CNS) and play a major role in the regulation of brain homeostasis. To maintain their cellular protein homeostasis, microglia express standard proteasomes and immunoproteasomes (IP), a proteasome isoform that preserves protein homeostasis also in non-immune cells under challenging conditions. The impact of IP on microglia function in innate immunity of the CNS is however not well described. Here, we establish that IP impairment leads to prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Induction of another immunoproteasome subunit β1i was recently shown to facilitate adaptation to mitochondrial stress and prevent formation of intracellular aggregates ( Kim et al, 2023 ). In β5iKO mice, impaired proteostasis with accumulation of ubiquitinated proteins was revealed in microglia ( Cetin et al, 2022 ). These findings are in line with the role of immunoproteasome in prevention of aggregate formation after stress ( Seifert et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of another immunoproteasome subunit β1i was recently shown to facilitate adaptation to mitochondrial stress and prevent formation of intracellular aggregates ( Kim et al, 2023 ). In β5iKO mice, impaired proteostasis with accumulation of ubiquitinated proteins was revealed in microglia ( Cetin et al, 2022 ). These findings are in line with the role of immunoproteasome in prevention of aggregate formation after stress ( Seifert et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…While proteasome-mediated suppression of inflammatory/immune responses might be an evolutionarily conserved phenomenon, the exact mechanisms of how immune responses are kept in check are likely to differ. For example, activation of type-I interferon signaling in mammals as a consequence of proteasome dysfunction has been attributed to ER stress and activation of the unfolded protein response (UPR) [ 28 , 50 , 51 ]. This is unlikely to be the case in the context of oomycete recognition as we have previously shown that introducing ER stress does not induce chil-27p :: GFP [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the cooperative model for immunoproteasome assembly, LMP7 subunit has a central role, as the lack of this subunit impairs the incorporation of LMP2 and MECL-1 into newly synthetized proteasome complex (Griffin et al, 1998). Recently, mice deficient in LMP7 were shown to have an impairment in proteotoxic stress related to defective microglial function (Cetin et al, 2022). However, only the complete deficiency of all three immunoproteasome subunits results in age-related epileptic seizures, suggesting that mice lacking LMP7 have still a relatively functional ubiquitin-proteasome system.…”
Section: Discussionmentioning
confidence: 99%